Zarządzenia tymczasowe a postanowienia z art, 443 k.p.c. wydawane w toku procesu o rozwód - Iżykowski, Michał (Wydział Prawa i Administracji UAM, 1982)
With an intent to attain security for claim the Polish Code of Civil Procedure provides a possibility of issuing legal decisions called provisional court orders. According to the regulation of the section 730 et seq. of the Code of Civil Procedure (hereinafter called the ccp) the provisional court order can be issued whenever there is a justified doubt arises that the creditor's claim cannot be satisfied or there is a fear, on the side of the creditor, of other legal effects of the court's final decision. Apart from the above regulation the Polish ccp in the section 443 provides for special rulings of a provisional character in the course of divorce litigation. These are designed for settlement of relations between husband and wife pending the action. The Polish doctrine has not settled whether the rulings within the meaning of section 443 of the ccp belong to a group of provisional court orders or they constitute a separate category of court decisions. In order to solve this question the author compares objectives of giving respective decisions, conditions (grounds) of their issuing, the scope and stability of findings, the course of proceedings to take evidence and other matters of procedure. Upon ascertainment of the existence of substantial differences, the author concludes that provisional court orders and rulings within the meaning of the section 443 of the ccp are in fact two distinct types of court decision.
Interim Orders and Provisions of the Article 443 of the Civil Procedure Code Enacted in the Course of Divorce Trial